2012
DOI: 10.1093/aje/kws336
|View full text |Cite
|
Sign up to set email alerts
|

Job Strain as a Risk Factor for Leisure-Time Physical Inactivity: An Individual-Participant Meta-Analysis of Up to 170,000 Men and Women: The IPD-Work Consortium

Abstract: Unfavorable work characteristics, such as low job control and too high or too low job demands, have been suggested to increase the likelihood of physical inactivity during leisure time, but this has not been verified in large-scale studies. The authors combined individual-level data from 14 European cohort studies (baseline years from 1985–1988 to 2006–2008) to examine the association between unfavorable work characteristics and leisure-time physical inactivity in a total of 170,162 employees (50% women; mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
200
3
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(217 citation statements)
references
References 49 publications
10
200
3
4
Order By: Relevance
“…Such work designs are associated with, for example: better physical well-being, including physical fitness (Fransson et al, 2012), lower hypertension (Babu et al, 2014), fewer headaches/ gastrointestinal problems (Nixon, Mazzola, Bauer, Krueger, & Spector, 2011) and lowered incidence of musculoskeletal disorders (Eijckelhof et al, 2013); higher mental health and psychological well-being (Luchman & González-Morales, 2013); more positive job attitudes, such as job satisfaction and organizational commitment (Humphrey et al, 2007); better job performance (Humphrey et al, 2007); and higher levels of innovation (Hammond, Neff, Farr, Schwall, & Zhao, 2011). Studies also show positive effects at higher levels in the organization, such as group work design enhancing team effectiveness (Campion, Papper, & Medsker, 1996;Xanthopoulou, Bakker, Demerouti, & Schaufeli, 2009) and team innovation (Hülsheger, Anderson, & Salgado, 2009).…”
Section: Mainstream Research: How Work Design Affects Outcomesmentioning
confidence: 99%
“…Such work designs are associated with, for example: better physical well-being, including physical fitness (Fransson et al, 2012), lower hypertension (Babu et al, 2014), fewer headaches/ gastrointestinal problems (Nixon, Mazzola, Bauer, Krueger, & Spector, 2011) and lowered incidence of musculoskeletal disorders (Eijckelhof et al, 2013); higher mental health and psychological well-being (Luchman & González-Morales, 2013); more positive job attitudes, such as job satisfaction and organizational commitment (Humphrey et al, 2007); better job performance (Humphrey et al, 2007); and higher levels of innovation (Hammond, Neff, Farr, Schwall, & Zhao, 2011). Studies also show positive effects at higher levels in the organization, such as group work design enhancing team effectiveness (Campion, Papper, & Medsker, 1996;Xanthopoulou, Bakker, Demerouti, & Schaufeli, 2009) and team innovation (Hülsheger, Anderson, & Salgado, 2009).…”
Section: Mainstream Research: How Work Design Affects Outcomesmentioning
confidence: 99%
“…Predefined, harmonized measures were used to assess job strain (yes v. no) and 4 life style risk factors at baseline: current smoking (yes v. no), 19 physical inactivity (yes v. no), 20 heavy drinking (≥ 21 and ≥ 28 units of alcohol per wk for women and men, respectively), 21 and obesity (body mass index [BMI] ≥ 30). 22 A detailed description of these measures, including their validation and harmonization, has been published previously.…”
Section: Measurement Of Job Strain and Lifestyle Risk Factorsmentioning
confidence: 99%
“…We found that those experiencing job strain were more likely to become physically inactive as assessed via questions on leisure time activity, compared to those free of job strain (22). Using cross-sectional data, we also found a link between job strain and obesity, however, in longitudinal analyses a temporal sequence from job strain to obesity was not confirmed (20).…”
Section: What Is the Par Of Job Strain For Chd?mentioning
confidence: 55%